Cover Image, Volume 29, Issue 7. Issue 7 (13th June 2019) - Ito, Hidenori; Morishita, Rika; Mizuno, Makoto; Tabata, Hidenori; Nagata, Koh‐ichi
Abstract : Cover legend: This cover image is based on the Research Article Rho family GTPases, Rac and Cdc42, control the localization of neonatal dentate granule cells during brain development by Hidenori Ito et al., DOI:10.1002/hipo.23047 .